2022
DOI: 10.1002/ange.202202328
|View full text |Cite
|
Sign up to set email alerts
|

A Crystalline Partially Fluorinated Triazine Covalent Organic Framework for Efficient Photosynthesis of Hydrogen Peroxide

Abstract: A partially fluorinated, metal‐free, imine‐linked two‐dimensional triazine covalent organic framework (TF50‐COF) photocatalyst was developed. Fluorine (F)‐substituted and nonsubstituted units were integrated in equimolar amounts on the edge aromatic units, where they mediated two‐electron O2 photoreduction. F‐substitution created an abundance of Lewis acid sites, which regulated the electronic distribution of adjacent carbon atoms and provided highly active sites for O2 adsorption, and widened the visible‐ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The development of highly active and low-cost COF photocatalysts is now an international research focus, bridging the fields of chemistry, material science, catalysis, and engineering 9 13 . To obtain high-performance COF photocatalysts, researchers are now exploring ways of increasing the visible-light absorption range 14 16 , optimizing band structures 17 20 , and decreasing the recombination of photogenerated electrons and holes 21 23 . Common strategies for achieving these performance-boosting properties include (i) incorporating a photosensitizer into the framework for improving the light-harvesting capability 24 27 ; (ii) functionalization of the linkers and tuning of the components to optimize the band gap energy and valence/conduction band potentials 17 , 28 31 ; (iii) construction of donor-acceptor moieties to improve charge transfer kinetics and charge carrier separation efficiencies 32 35 ; (iv) doping non-metal elements (N, P, S, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The development of highly active and low-cost COF photocatalysts is now an international research focus, bridging the fields of chemistry, material science, catalysis, and engineering 9 13 . To obtain high-performance COF photocatalysts, researchers are now exploring ways of increasing the visible-light absorption range 14 16 , optimizing band structures 17 20 , and decreasing the recombination of photogenerated electrons and holes 21 23 . Common strategies for achieving these performance-boosting properties include (i) incorporating a photosensitizer into the framework for improving the light-harvesting capability 24 27 ; (ii) functionalization of the linkers and tuning of the components to optimize the band gap energy and valence/conduction band potentials 17 , 28 31 ; (iii) construction of donor-acceptor moieties to improve charge transfer kinetics and charge carrier separation efficiencies 32 35 ; (iv) doping non-metal elements (N, P, S, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are another new type of emerging metal-free photocatalysts due to their well-defined pore structure, extended light-response range, and highly tunable optoelectronic property. Although several pioneering studies have shown that COFs could be endowed with promising photocatalytic H 2 O 2 production efficiency through molecular tailoring, topology tuning, mass transfer regulating, Lewis acid site manipulating, and biocatalytic approach mimicking, several critical issues need to be addressed before their practical implementation. First, the imine bonds are susceptible to harsh conditions, as a majority of the highly crystalline COFs were prepared using the reversible Schiff-base chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…For the highly efficient production and wide application of H2O2, metal-free semiconductors, as best exemplified by polymeric carbon nitrides (pCNs) of graphitic structure, have emerged many pioneering strategies for electronic structures engineering to enhance spatially separating redox with various molecular structures 3 or/and foreign dopants [28][29][30][31][32] . They have been envisaged as promising photocatalysts for the light-driven synthesis of H2O2 without any sacrificial reagents.…”
Section: Introductionmentioning
confidence: 99%